Essential work of fracture assessment of acrylonitrile butadiene styrene (ABS) processed via fused filament fabrication additive manufacturing - Verma, P; Ubaid, J; Schiffer, A; Jain, A; Martinez-Paneda, E; Kumar, S (Springer Nature, 2021)
Experiments and finite element (FE) calculations were performed to study the raster angle–dependent fracture behaviour of acrylonitrile butadiene styrene (ABS) thermoplastic processed via fused filament fabrication (FFF) additive manufacturing (AM). The fracture properties of 3D-printed ABS were characterized based on the concept of essential work of fracture (EWF), utilizing double-edge-notched tension (DENT) specimens considering rectilinear infill patterns with different raster angles (0°, 90° and + 45/− 45°). The measurements showed that the resistance to fracture initiation of 3D-printed ABS specimens is substantially higher for the printing direction perpendicular to the crack plane (0° raster angle) as compared to that of the samples wherein the printing direction is parallel to the crack (90° raster angle), reporting EWF values of 7.24 kJ m−2 and 3.61 kJ m−2, respectively. A relatively high EWF value was also reported for the specimens with + 45/− 45° raster angle (7.40 kJ m−2). Strain field analysis performed via digital image correlation showed that connected plastic zones existed in the ligaments of the DENT specimens prior to the onset of fracture, and this was corroborated by SEM fractography which showed that fracture proceeded by a ductile mechanism involving void growth and coalescence followed by drawing and ductile tearing of fibrils. It was further shown that the raster angle–dependent strength and fracture properties of 3D-printed ABS can be predicted with an acceptable accuracy by a relatively simple FE model considering the anisotropic elasticity and failure properties of FFF specimens. The findings of this study offer guidelines for fracture-resistant design of AM-enabled thermoplastics.